Performance Optimization - Pranoto, Wirandi; B, Mesra (PT. Multidisciplinary Press Indonesia, 2024)
This study aims to see the influence of work motivation and leadership style on employee performance through job satisfaction as a mediating variable at the BPJS Ketenagakerjaan, Sumbagut Regional Office. This type of research uses a qualitative method, this research was conducted at BPJS Ketenagakerjaan, Sumbagut Regional Office, the population used was 60 employees. The sample used was all populations of 60 employees with saturated samples as the sampling technique. The data sources used are primary data sources and data collection by distributing questionnaires. This research model uses phat analysis and the measuring instrument is the smart PLS application version 3.3.3. The results of this study are as follows: Leadership style has a positive and significant effect on job satisfaction with the original sample value of 0.276 and P values 0.000. Leadership style has a positive and insignificant effect on employee performance with the original sample value of 0.102 and p values 0.615. Job satisfaction has a positive and significant effect on employee performance with the original sample value of 0.737 and p values 0.000. Work motivation has a positive and significant effect on job satisfaction with the original sample value of 0.859 and p values 0.000. Work motivation has a positive and insignificant effect on employee performance with the original sample value of 0.001 and p values 0.999. Leadership style has a negative and insignificant effect on employee performance through job satisfaction indirectly with the original sample result of -0.199 and p values 0.095. Work motivation has a positive and significant effect on employee performance through job satisfaction with the original sample value of 0.630 and p values 0.000.